Inductions of physical education teachers in Europe - Hunuk, Deniz; Avsar, Zuleyha; Kupr, Jaroslav; Gobbi, Erica (Journal of Physical Education (Maringá), 2019)
The purpose of this research was to explore the similarities and differences of existing induction systems for physical education (PE) teachers in Europe. Physical education teacher education (PETE) experts from 25 European countries shared their PETE curricula and best practices in their induction systems. Data was collected through a semi-structured template that informed the experts’ presentation of the induction procedures and experiences in their respective countries. Question and answer sessions after each presentation allowed for clarification and further information to be collected. All presentations were thematically analysed. Results stated that in the majority of countries involved in this project, there is no coherent or systematic structured induction programmes for novice PE teachers. Some countries have developed a good system of induction, some are trying to develop it however in most cases, in some reasons, those systems are relatively unsystematic and not fully embedded in their education system. Clearly, there is a need for a systematic model of a culture of induction of novices PE teachers in the teaching profession in individual countries. The present research on induction can help teacher education program developers to design educative, cost-effective opportunities for novice PE teachers by context adapting and replicating existing successful programs.